A Systematic Literature Review: The Impact of the Use of E-Money as a Non-Cash Payment Instrument on the Stability of the Indonesian Financial System - Apriani, Mita; Antika, Reni; Haerani, Sarah; Chaidir, Taufiq (Journal of Finance, Economics and Business, 2024)
This research aims to analyze the impact of the use of electronic money (e-money) on financial system stability in Indonesia. This research uses a systematic literature study method to evaluate various relevant studies related to the use of e-money and its effect on financial stability. The main variables analyzed include payment system efficiency, financial inclusion, cybersecurity, and reliance on technological infrastructure. The results show that e-money has a positive impact on financial system stability through increasing transaction efficiency and expanding access to formal financial services, especially for people who previously did not have access to banks. There are also negative impacts associated with the use of e-money, such as cybersecurity risks and dependence on technological infrastructure. Therefore, strict regulations by regulators such as Bank Indonesia and the Financial Services Authority (OJK) are needed to mitigate these risks, as well as increase public awareness of the importance of maintaining financial system stability and security in the use of e-money.